2020
DOI: 10.3390/su12156222
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure, Financial Performance, and Sustainability of Micro-Finance Institutions (MFIs) in Bangladesh

Abstract: Capital structure plays an important role in organizational performance. Sources of funds for micro-finance institutions (MFIs) and their performance and financial sustainability become an important topic for the MFIs and poverty alleviation initiatives to achieve sustainable development goals of the UN. We explored the following question: Does the financial structure in terms of financial leverage affect the financial performance: Financial sustainability, depth, and breadth of outreach of MFIs? Our research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 55 publications
(74 reference statements)
2
45
0
Order By: Relevance
“…The logistic model has shown that microfinance capital sources influence farmers' access to microfinance credit with marginal effects of 0.0693(6.9%) ( Table 3). This correlation is consistent with previous studies that found that microfinance capital structure has a close relationship with its financial performance (Parvin et al , 2020;Tchuigoua, 2015;Wagner and Winkler, 2013). The study found out microfinance institutions that rely on external debt are likely to fail to perform their core business to help the poor and threatening the ability to give out credit to their clients.…”
Section: Estimating Results: Sources Of Capitalsupporting
confidence: 91%
See 1 more Smart Citation
“…The logistic model has shown that microfinance capital sources influence farmers' access to microfinance credit with marginal effects of 0.0693(6.9%) ( Table 3). This correlation is consistent with previous studies that found that microfinance capital structure has a close relationship with its financial performance (Parvin et al , 2020;Tchuigoua, 2015;Wagner and Winkler, 2013). The study found out microfinance institutions that rely on external debt are likely to fail to perform their core business to help the poor and threatening the ability to give out credit to their clients.…”
Section: Estimating Results: Sources Of Capitalsupporting
confidence: 91%
“…Sources of microfinance capital play a significant role. In most cases, different capitalization determines financial strength (Parvin et al, 2020). A weak source or overreliance on the donor is likely to affect microfinance operation and credit distribution (Bhanot and Bapat, 2015;Al-Mamun et al, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Shepherd and DeTienne (2005) showed a positive relationship between the number of opportunities identified and financial reward, which means opportunity identification is positively related to the financial rewards (Gielnik et al, 2018). In the growing Bangladeshi economy, where newer markets and niches are emerging, a firm's financial performance depends on how well the entrepreneur can scan the market and environment and find his position in this scene (Parvin et al, 2020). Bangladeshi restaurant firms are mainly service-providing firms that provide the best possible eating-out experience compared with the context.…”
Section: Resultsmentioning
confidence: 98%
“…Basically, community economic grouping and organizing is aimed at gaining access to capital in existing financial institutions to develop economic enterprises. Facilitation and support for business capital through microcredit packages, including savings, insurance and other financial services, will encourage the development of economic enterprises by the poor [66]. Furthermore, the development of the scale of community economic enterprises will be related to the functions and roles of institutions.…”
Section: Economic Business Development and Strengthening Community Capacitymentioning
confidence: 99%